Fragments of Voices: Poetic Inquiry as a Method for Collaborative Meaning Making - Wikström, Hannes ; 0009-0008-7458-8229 (European Association of Music in Schools: 33rd EAS Conference Vienna 2026, Austria, 2026-04-08 - 2026-04-11, 2026)
This workshop presents an interactive and participant-oriented form of poetic inquiry that invites active and collaborative exploration of student voices through artistic, hands-on engagement. By combining ideas from concrete and graphic poetry – such as those of the pioneering poet and theorist Mary Ellen Solt – with principles of arts-based and participatory research, the session introduces a method of poetic inquiry that turns data into collaborative reflection. During the workshop, participants teachers, students, or researchers – are encouraged to create their own concrete (graphic) poems using words and fragments derived from transcripts of student interviews. Drawing on the well-known concept of “Fridge Poetry” or “Magnetic Poetry”, the comparative act of combining in vivo statements (words and sentences derived from raw data) is presented as a creative analytical tool, particularly suited to dialogic group processes where the interpretation of student voice is in focus. The method showcased has been developed and utilised within a PhD project in music education, focusing on interdisciplinary, project-based learning in the Swedish Arts and Music School. All research participants are fully anonymised in the “magnetic-poetry kit” used during the session. Workshop participants will also have the opportunity to create their own samples of “poetic magnets” – ideal for those wishing to bring home a concrete idea for their own educational/researcher practice. Ultimately, the workshop demonstrates a playful yet rigorous method with potential to foster democratic participation, strengthen social cohesion, and inspire collaboration across educational communities.